Audiovisual Translation in a Global Context
XVII, 291 p.
Keywords: This book offers an up-to-date survey of the present state of affairs in Audiovisual Translation, providing a thought-provoking account of some of the most representative areas currently being researched in this field across the globe. The book discusses theoretical issues and provides useful and practical insights into professional practices.